Grey prediction control and extension assessment for turbine governing system. Issue 11 (1st August 2016) - Wang, Mingdong; Zhang, Yunpeng; Ji, Tian; Wang, Xueke
Abstract : The authors present a control method for generator speed control system based on the grey prediction theory, to solve the stability problem of power system in various perturbations. The results of the simulation indicate that with grey prediction control, the control system behaves less adjusting time and less overshoot. That is, grey prediction control is superior. Besides, the authors establish a control system performance index evaluation system to analyse the performance of grey prediction controller quantitatively. The extension evaluation method is employed to evaluate grey prediction control contrasted to conventional control, and the result shows that the control effect of former is better than the latter, which confirmed the validity of grey prediction method for turbine speed control system.